1997
DOI: 10.1017/s0031182097001546
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a partial sequence encoding a novel Schistosoma mansoni serine protease

Abstract: A PCR strategy using degenerate oligonucleotide primers based upon consensus sequences of the active site of serine proteases yielded a 467 bp fragment from genomic DNA from Schistosoma mansoni cercariae. The sequence presented a continuous open reading frame and the deduced amino acid sequence (156 aa) presented homologies with various serine proteases, in particular the highest percentage identity was observed with a mammalian plasma kallikrein. The expression of this serine protease was studied first at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This number is significantly lower than the 135 family S1 proteases found in the human genome [8], [25] and may be due to the lack of need to regulate the more complex and expanded physiological processes found in vertebrates [55]. In our study and apart from SmSP1 [13], [14], we identified four additional SmSP genes encoding typical sequence features of the S1 family [7], [8] and which we term SmSP2 through SmSP5. Two further genes (Smp_194090 and Smp_06530 in GeneDB) were identified in the S. mansoni GeneDB as putative proteolytically inactive SmSPs as they lack the catalytic serine or histidine residue in the catalytic triad.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…This number is significantly lower than the 135 family S1 proteases found in the human genome [8], [25] and may be due to the lack of need to regulate the more complex and expanded physiological processes found in vertebrates [55]. In our study and apart from SmSP1 [13], [14], we identified four additional SmSP genes encoding typical sequence features of the S1 family [7], [8] and which we term SmSP2 through SmSP5. Two further genes (Smp_194090 and Smp_06530 in GeneDB) were identified in the S. mansoni GeneDB as putative proteolytically inactive SmSPs as they lack the catalytic serine or histidine residue in the catalytic triad.…”
Section: Discussionmentioning
confidence: 76%
“…The five remaining SmSP genes, including the previously sequenced and partially characterized SmSP1 [13], [14], were cloned and sequenced. The other four gene sequences named SmSP2 through SmSP5 (Table 1) were significantly corrected and re-annotated in the primary database ( S. mansoni GeneDB) due to various sequence inaccuracies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study identified a serine protease from S. mansoni cercariae genomic DNA: a kallikrein-like protease [ 176 ]. The same research group isolated the serine protease SmSP1 from S. mansoni , which presents homology with mouse plasma kallikrein and human factor I light chain.…”
Section: Kinins and Their Implication In Protozoan And Parasite Inmentioning
confidence: 99%